Pea Leafminer, Liriomyza huidobrensis (Blanchard) (Insecta: Diptera: Agromyzidae) - Gary J. Steck (EDIS, 2002)
This document is EENY-111 (originally published as DPI Entomology Circular No. 378), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 1999.